THE ROLE OF OMICS RESEARCH IN GERMPLASM CONSERVATION - Yaya Rukayadi (Prosiding Seminar Nasional Biotik, 2022)
The word omics refers to a field of study in biological sciences that ends with -omics, such as genomics, transcriptomics, proteomics, or metabolomics. The ending -ome is used to address the objects of study of such fields, such as the genome, proteome, transcriptome, or metabolome, respectively. In relation to the conservation of germplasm, genomics-based plant germplasm research has been carried out and has been proven to be able to conserve germplasm. Recently, to conserve germplasm using only genomics-based plant germplasm research, it is felt to be incomplete, because not all genes can be expressed under certain conditions. For this reason, other omics such as proteomics and metabolomics play an important role in the conservation of germplasm. In this paper, the role of other omics research, especially metabolomics is described.